2011
DOI: 10.1016/j.hal.2011.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of activity and partial characterization of large non-proteinaceous lytic allelochemicals produced by the marine dinoflagellate Alexandrium tamarense

Abstract: Certain strains of the toxigenic dinoflagellate Alexandrium tamarense produce potent allelochemicals with lytic activity against a wide variety of marine microorganisms. Our efforts to characterize these allelochemicals from a lytic strain focused on the less polar components because of their higher lytic activity.Fractionation and partial purification after solid phase extraction (SPE) were achieved via alternative chromatographic methods, namely HPLC separation on C8 and HILIC phases. Through MALDI-TOF mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 46 publications
(50 reference statements)
0
37
0
Order By: Relevance
“…After standing for 1 h, the precipitate was collected by centrifugation, dissolved in 100 ml of 1 M HCl, and dialyzed in 0.1 mM HCl for 3 days. According to the previous findings (Yamasaki et al, 2008;Ma et al, 2011), some amphipathic extracellular substances with large molecular weights may be responsible for the allelopathic action of A. tamarense. Additionally, Emura et al (2004) isolated a protein-like hemolytic compound with a molecular weight of more than 10 kDa by dialysis from Alexandrium taylori.…”
Section: Extraction Of Extracellular Toxins From a Tamarense Culturesmentioning
confidence: 82%
See 2 more Smart Citations
“…After standing for 1 h, the precipitate was collected by centrifugation, dissolved in 100 ml of 1 M HCl, and dialyzed in 0.1 mM HCl for 3 days. According to the previous findings (Yamasaki et al, 2008;Ma et al, 2011), some amphipathic extracellular substances with large molecular weights may be responsible for the allelopathic action of A. tamarense. Additionally, Emura et al (2004) isolated a protein-like hemolytic compound with a molecular weight of more than 10 kDa by dialysis from Alexandrium taylori.…”
Section: Extraction Of Extracellular Toxins From a Tamarense Culturesmentioning
confidence: 82%
“…Though many studies have been performed, the nature of allelochemicals involved in the allopathic action of Alexandrium tamarense remains unclear (Emura et al, 2004;Grané li et al, 2008;Yamasaki et al, 2008;Ma et al, 2011). Some large amphipathic extracellular substances, independent of known phycotoxins, PSP toxins and spirolides, have been recommended to be responsible for the action (Tillmann and John, 2002;Emura et al, 2004;Tillmann et al, 2007;Yamasaki et al, 2008;Ma et al, 2011).…”
Section: Allelochemicals In a Tamarensementioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that some Alexandrium spp. strains are able to produce extracellular toxic compounds (Arzul et al, 1999) known to have allelopathic activity on algae (Ma et al, 2011;Lelong et al, 2011) and ichtyotoxic activity on bivalves (Ford et al, 2008;Borcier et al, 2017;Castrec et al, 2018). Recent studies using the AM89BM A. minutum strain (used in the dataset 3) suggested that these compounds might also negatively affect feeding behavior in Pecten maximus (Borcier et al, 2017) and C. gigas (Castrec et al, 2018).…”
Section: ρ Ps T Parametermentioning
confidence: 99%
“…has been shown to affect membrane integrity, mobility via loss of flagella and/or cell survival against a wide variety of other microalgae (Arzul et al, 1999;Tillmann et al, 2008;Tillmann and Hansen, 2009), heterotrophic protists (Hansen et al, 1992;Matsuoka et al, 2000;Tillmann and John, 2002) and diverse members of microbial communities (Weissbach et al, 2011). Although molecular structures and exact mode of action of allelochemicals from Alexandrium still are poorly known (Ma et al, 2009;Ma et al, 2011), all evidence suggest that the lytic activity against target protists is not related to the known toxins, such as saxitoxins and spirolides, produced among members of this genus (Tillmann and John, 2002;Tillmann et al, 2007).…”
Section: Lytic Activitymentioning
confidence: 99%